Environmental Pollution and our Responsibilities in the Light of Sīrah al Nabī ﷺ - Abdullah, Muhammad Farooq (Journal of Islamic and Religious Studies, 2021)
The creation of the universe and maintaining it on a certain balance is called the nature of Allah Almighty. Allah has made the human being the trustee of this natural environment and has guided humanity in the basic principles of natural needs and purposes. Unnecessary interference in natural resources causes environmental pollution, which has created countless problems today. The paper intends to provide the solution of the causes of this catastrophe and it's remedied in the light of the teachings of the Holy Prophet. The Holy Prophet (PBUH) has laid down several principles for the survival of humanity and the fulfillment of its natural needs. It is an inescapable fact that the Prophet (PUBH) drew attention to environmental protection and preservation of the environment at a time when man did not realize its importance, and it is also a fact that if humanity today follows the teachings of the Holy Prophet, environmental protection and prevention of pollution can be ensured. The study concludes that if one lives in the light of the principles and rules laid down by the Holy Prophet, the good life in this world can be achieved along with the eternal success of the hereafter. The research recommends the government, scholars and media to run a campaign for awareness about the environmental problems in their domains.